Designing Mobile Application for the Over the Counter Drug Marketing - Vasja Roblek; Meško Maja (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The increased usage of mobile apps has a great potential in Pharmacy market. Through the use of mobile apps, web portals and social media may allow a fast and wide diffusion of awareness for over the counter (OTC) drugs and attract a large number of customers, thus increasing the value of searching for information, quality and lower costs of the purchase. The goal of this paper is to identify the key factors as antecedents of customer satisfaction for the design of a mobile app for OTC drug marketing. To this aim, the authors use the Kano model that allows categorizing service attributes according to how they are perceived by customers and estimating their impact on customer satisfaction. This model is adopted in order to identify, express and latent needs of customers and to design a mobile app for OTC marketing according to their perceptions and expectations. To apply the Kano model, the authors used quantitative data collected through 537 questionnaires that were sent to the Slovenian internet users (June and August 2013). The results of this analysis can be relevant to the pharmaceutical companies; drugs vendors and marketing managers plan strategy and operational activities, for pharmaceutical companies in the field of OTC drugs marketing, for application developers, and for all those concerned with OTC drugs marketing issues.
Keywords: M10; M31; F14; K23; L65; L81; 330; OTC drugs; mobile applications; Kano model; customer satisfaction; mobile marketing